Dissolved Oxygen Strategy for Synthesizing MnO2 and its Application for Circulating Wastewater Treatment. Issue 48 (21st December 2022) - Xia, Zi‐Wei; Zheng, Jing; Zhang, Min; Yin, Xue‐Bo
Abstract: Manganese dioxide (MnO2 ) is promising and widely used for catalytic oxidation, energy conversion/storage, environmental remediation, and biomedicine. Its synthesis has been extensively concerned, but strong oxidants, high temperature, and long reaction time are often required. Here we proposed the dissolved oxygen strategy for oxidization of Mn 2+ at pH 12 to obtain MnO2 with green, high feasibility, and low cost. The oxygen dissolved in water was used as oxidant to oxidize Mn 2+ ions at pH 12 for the formation of MnO2 heated at 55 °C for 1 h. The process is confirmed with the theoretical calculation from Nernst equation. The precipitate was collected and dried as MnO2 with small particles with large amounts of oxygen defective sites as validated with XPS, SEM, BET, and XRD results. Our MnO2 exhibits higher oxidation capacity than commercially available MnO2 as confirmed with the oxidization of methylene blue and streptomycin. By adjusting the temperature and pH, the organics were removed and MnO2 become Mn 2+ ions again. Thus, we proposed a circulating water treatment strategy as the produced Mn 2+ was transferred into MnO2 again after adjusted pH to 12 and thermal treatment. We hope the simple and green preparation strategy of MnO2 with low cost can expand the applications of MnO2 . Abstract : We proposed the dissolved oxygen strategy for oxidization of Mn 2+ at pH 12 to obtain MnO2 with green, feasibility and low cost and MnO2 was applied for degradation of organic matters, such as methylene blue (MB).